2023
DOI: 10.1155/2023/7707452
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of CdSe Quantum Dots Show Biochemical and Oxidative Damage in Wistar Rats

Abstract: Cadmium selenium quantum dots (CdSe QDs) with modified surfaces exhibit superior dispersion stability and high fluorescence yield, making them desirable biological probes. The knowledge of cellular and biochemical toxicity has been lacking, and there is little information on the correlation between in vitro and in vivo data. The current study was carried out to assess the toxicity of CdSe QDs after intravenous injection in Wistar male rats (230 g). The rats were given a single dose of QDs of 10, 20, 40, and 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
(67 reference statements)
3
4
0
Order By: Relevance
“…Although the significant decrease in CAT activity could indicate a high amount of hydrogen peroxide, we should take into consideration that the increase in GPx activity after the first 6 h of exposure could actually suggest that the hydrogen peroxide was maintained at a low level based on the difference in K M for this substrate between these two enzymes. Similar results regarding the hepatic CAT activity after QDs administration have also been reported by Das et al [ 42 ]. The transient increase in SOD activity at 6 h after administration might be due to either indirect activation by SiQDs, stimulating the production of superoxide anion in the cells and activating the antioxidant defense mechanisms in order to counteract the radicals; or due to the alteration of gene expression involved in SOD synthesis.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Although the significant decrease in CAT activity could indicate a high amount of hydrogen peroxide, we should take into consideration that the increase in GPx activity after the first 6 h of exposure could actually suggest that the hydrogen peroxide was maintained at a low level based on the difference in K M for this substrate between these two enzymes. Similar results regarding the hepatic CAT activity after QDs administration have also been reported by Das et al [ 42 ]. The transient increase in SOD activity at 6 h after administration might be due to either indirect activation by SiQDs, stimulating the production of superoxide anion in the cells and activating the antioxidant defense mechanisms in order to counteract the radicals; or due to the alteration of gene expression involved in SOD synthesis.…”
Section: Discussionsupporting
confidence: 90%
“…After a dose-dependent decrease in SOD activity after the first hour, an increase in this enzyme’s activity compared with the control was measured after 6 h, suggesting that SOD was vulnerable at the beginning of exposure due to superoxide anion generation; however, antioxidant defense mechanisms were further activated to neutralize the free radicals. Nevertheless, this mechanism was not enough to counteract the oxidative stress as we could observe a decrease in SOD activity after 24 and 72 h. A previous report of Das et al [ 42 ] showed the same reduction in renal SOD activity after CdSe QD administration at a high dose to rats. This pattern of activity dynamics was also evidenced in the case of Gred and GPx, showing that the balance between GSH utilization and regeneration was perturbed, as it was confirmed by the dose- and time-dependent decrease in GSH levels.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…These newly developed non-Cd QDs exhibit improved blood half-life and minimal reticuloendothelial system (RES) uptake. 25 QDs toxicity has also been studied by using different animal models, such as zebrafish, 26 xenopus, 27 mouse, 28 rat 29 , 30 and macaque. 31 …”
Section: Introductionmentioning
confidence: 99%